E-Commerce in Singapore and Indonesia: Comparison of Policies - Sahya Anggara; Zang Cao (GoAcademica Research & Publishing, 2019)
New media is a term that refers to products and services that provide information/entertainment using computers or the internet. The emergence of new media also encourages other activities that people usually do in a conventional way to the cyber world. Doing business is one example. Electronic commerce, or also known as e-commerce, is a trading method that uses the internet. Nowadays, e-commerce has become a trend in the world. Comprehensive regulations are needed to manage this activity. This paper will try to describe a comparative public policy on e-commerce in the two ASEAN countries, Singapore and Indonesia. We will see differences in e-commerce development in both countries, and attention to the role of governments as decision-makers in both countries.